Menurunkan Perilaku Maladaptif Pada Gangguan Skizoafektif dengan Behavioral activation - Tiara Maulida; Adhyatman Prabowo (Universitas Muhammadiyah Malang, 2023)
Schizoaffective disorder is a serious mental disorder that combines symptoms of schizophrenia with mood symptoms such as depression or mania. The main symptom of this disorder is affection problems, with possible motor movement and behavioral disorders. The study aims to develop effective treatment to reduce maladaptive behavior with behavioral activation. Assessment methods used through test and non-test techniques. Behavioral activation is a therapeutic approach that aims to overcome disorders by increasing positive activity and changing behavior patterns that hinder emotional well-being. The results showed that behavioral activation can reduce maladaptive behavior of schizoaffective disorder. This meant that the duration of the subject's maladaptive behavior decreased as the intervention progresses until the end of the intervention. Gangguan skizoafektif adalah gangguan mental serius yang menggabungkan gejala skizofrenia dengan gejala suasana hati seperti depresi atau mania. Gejala utama gangguan ini adalah masalah kasih sayang, dengan kemungkinan gangguan gerak motorik dan perilaku. Penelitian ini bertujuan untuk mengembangkan pengobatan yang efektif untuk mengurangi perilaku maladaptif dengan aktivasi perilaku. Metode penilaian yang digunakan melalui teknik tes dan non tes. Aktivasi perilaku merupakan pendekatan terapeutik yang bertujuan untuk mengatasi gangguan dengan meningkatkan aktivitas positif dan mengubah pola perilaku yang menghambat kesejahteraan emosional. Hasil penelitian menunjukkan bahwa aktivasi perilaku dapat menurunkan perilaku maladaptif gangguan skizoafektif. Artinya, durasi perilaku maladaptif subjek menurun seiring berjalannya intervensi hingga akhir intervensi.